Effect of moderate-intensity exercise on inflammatory markers among postmenopausal women - Chagas, Eduardo Federighi Baisi; Bonfim, Mariana Rotta [UNESP]; Turi, Bruna Camilo [UNESP]; Brondino, Nair Cristina Margarida [UNESP]; Monteiro, Henrique Luiz [UNESP] (Human Kinetics, 2017)
Background: Declines in ovarian function in postmenopausal women may contribute to increase inflammatory cytokines, which can lead to chronic diseases. However, studies have shown that exercise interventions are important to manage inflammatory conditions. Thus, the objective of this study was to analyze the effect of exercise intervention on inflammatory markers among obese and postmenopausal women. Methods: 70 women composed the sample (Exercise group [EG; n = 35] and nonexercise group [nEG; n = 35]). IL-6, TNF-α, and IL-10 were the inflammatory markers analyzed. Exercise program was 20 weeks long and consisted of aerobic and neuromuscular training. Data about chronic diseases, medication use, dietary intake, body composition and biochemical variables were collected. Results: EG showed significant reductions in body mass index, waist circumference and body fat percentage, as well as increased lean body mass. EG showed significant reductions in TNF-α and significant interaction between group and intervention time. Reductions in IL-10 were identified only in nEG. Substantial effect of exercise intervention was observed with increased ratio of IL-10/IL-6 and IL-10/TNF-α. Conclusions: Combination of aerobic exercise and resistance training was effective in reducing inflammation. Thus, implementation and maintenance of similar exercise programs can contribute to reduce chronic inflammation among obese postmenopausal women.
Keywords: Chronic disease; Obesity; Public health